EFFECT OF NITROGEN FERTIGATION AND BAND PLACEMENT FERTILIZER APPLICATION ON SOIL-LEAF NUTRIENT BUILD-UP AND INCREMENTAL GROWTH OF ACID LIME - Shirgure, P.S; srivastava, A.K.; Singh, Shyam (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted on pre-bearing acid lime plants for evaluating the efficacy of differential nitrogen fertigation and band placement method of fertilizer application on soil-leaf nutrient built-up as well as incremented growth of the plant. The treatments consisted of fertigation with 60 %, 80 % and 100% N of recommended dose and band placement with 100 % N of recommended dose as control. The plants were fertigated using nitrogen (Urea) fertilizer monthly and phosphorous and potassium were given with band placement. The soil available N built up was more in fertigation with 80 % N treatment during 1995-97 followed by fertigation with 100% N band placement and fertigation with 60% N. The available P built-up in the soil was highest in band placement followed by fertigation with 100% N fertigation with 80% N. The available P in the soil was decreased in fertigation with 60% N. The available K built-up in the soil was more in fertigation with 100% N followed by band placement, fertigation with 80% N and fertigation with 60% N. The available leaf N built-up was highest in fertigation with 80% N followed by fertigation with 100% N. fertigation with 60% N and band placement during 1995 to 1997. The leaf P built was decreased in all the treatments. The highest depletion was recorded in fertigation with 60% N followed by fertigation with 80% N, band placement and fertigation with 100% N.The available K built up in the acid lime leaves was more in fertigation with 80% N followed by fertigation with 100% N fertigation with 60% N and band placement. The incremental plant height was more in fertigation with 80% N (90.34 cm) followed by fertigation with 60% N (8715 cm), band placement (81.3 cm) and fertigation with 100% N (81.1 cm) and fertigation with 100% N (81.1 cm) during 1995-97. The incremental stock girth was more in fertigation with 100% N (17.9 cm) and ranged from 17.1 to 17.3 cm in other treatments. The canopy volume of acid lime plant was highest in fertigation with 80% N (5.11 in') followed by 4.9 tre in fertigation with 60% N and band placement and 4.4 ne in fertigation with 100% N. The results revealed that the soil-leaf nutrient built up and incremental plant growth was superior in N fertigated plants than band placement method of fertilizer application .